Epidemiology of Aortic Dissections – Understanding the Aortic Catastrophe - Gouveia e Melo, Ryan (2023)
Acute aortic dissections are unpredictable aortic catastrophes. Although significant recent improvements have been accomplished in the treatment and management of aortic dissections, a significant amount is still not fully understood regarding this deadly condition. Comprehension of aortic dissections is especially important due to the impact of the disease, since a lot of patients die before reaching the hospital and a significant number of the ones who do survive the initial event end up dying during follow-up. The epidemiology and disease characteristics of these conditions are still under investigation and not completely clear. In this article we aim to review the current knowledge on the epidemiology and clinical characteristics of aortic dissections.